2023
DOI: 10.1007/s10671-023-09342-7
|View full text |Cite
|
Sign up to set email alerts
|

Student access to technology at home and learning hours during COVID-19 in the U.S

Abstract: Studies have shown that the digital divide affects students' educational achievement across racial and ethnic groups. In light of this, the study investigates the effect of technology access at home on student learning hours during the COVID-19 pandemic and across racial and ethnic groups in the U.S. The Household Pulse Surveys (HPS), conducted by the United States Census Bureau and administered from August 19, 2020, to March 29, 2021, were used for the analysis. We compute a composite index of technology acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Much of the data collected showed this to be due to poverty and low-income-related issues, which included students not being ready for college. Although the number of students attending college right after the high school dropped, the Education Department has also concluded that by the end of 2020, 2/3 of jobs will require at least the completion of post-secondary education or training (Alsarayreh, 2023;Haderlein, et al, 2021;Ogundari, 2023).…”
Section: Responding To the New Paradigm In Teachingmentioning
confidence: 99%
“…Much of the data collected showed this to be due to poverty and low-income-related issues, which included students not being ready for college. Although the number of students attending college right after the high school dropped, the Education Department has also concluded that by the end of 2020, 2/3 of jobs will require at least the completion of post-secondary education or training (Alsarayreh, 2023;Haderlein, et al, 2021;Ogundari, 2023).…”
Section: Responding To the New Paradigm In Teachingmentioning
confidence: 99%
“…The last aspect was waived because of the technological culture present at the university where the study was conducted (students/teachers/training programs). Despite this, the last aspects are not true in general under different educative contexts (Ogundari, 2023). Transitions in terms of self-assessment, particularly going on the "New Normal" period, smoothing such transition for students have become a crucial factor to correctly evaluate online education, but also the real background of skills, discipline, and knowledge in higher education students.…”
Section: Research Limitations Practical and Theoretical Implicationsmentioning
confidence: 99%